Students needs, parents, and teachers’ perceptions about spending their free time (Memorias Sifored - Encuentros Educación UAN, 2023)
The purpose of this research is to identify students’ needs, parents, and teachers’ perceptions about how students use their free time. This research took place at Liceo Mayor de Palermo in Bogotá, Colombia, with vulnerable children between eight and sixteen years old. The main variables identified by the authors were parents and teachers’ perceptions, students’ needs and academic engagement.  A mixed approach from an analytical cross-sectional study in which the main research techniques applied were three different questionnaires for students, parents, and teachers. Some preliminary findings show that students have around 2 – 6 hours of free time after school in which they spend their time playing video games, watching movies or TV, and using electronic devices. Parents are so concerned about the way their children spend their time, excessive use of electronic devices and sedentary lifestyle.  Factors such as money, time, transportation, and safety do not allow them to attend after-school programs. This study seeks to provide information necessary to identify needs, perceptions, and justification for designing free after-school programs to create a safe, healthy, and beneficial environment for this population.
Keywords: tiempo libre; programas extraescolares; necesidades; percepciones